Antioxidant Activity of Ixora chinensis - Chen, Rui; Su, Wei; Li, Peiyuan; Huo, Lini; Lu, Rumei; Lu, Chengsheng (Asian Journal of Chemistry, 2012)
Ixora chinensis, a traditional Chinese medicine material, was extracted with different solvent. Their antioxidant activities were investigated using three tested systems in vitro, including DPPH, ABTS radical scavenging assay and reducing power assay. The acetone extract exhibited outstanding antioxidant activities. The results showed that the extracts of Ixora chinensis, especially acetone extract, possessed potent antioxidant activities, could be used as functional food and medicine materials.